1997
DOI: 10.1046/j.1525-1438.1997.00417.x
|View full text |Cite
|
Sign up to set email alerts
|

Adult granulosa-cell tumor of the ovary: a retrospective study of 45 cases

Abstract: This study describes 45 cases of adult granulosa-cell tumors seen in our institution between 1976 and 1993. The median age was 46.5 years (12-77) and 18 women were postmenopausal. Vaginal bleeding was present in one-third of cases; other complaints were abdominal pain (28%) and the presence of a pelvic mass (47%). The tumor size was variable (<3 cm to 30 cm, median 11.5 cm). FIGO stages were: stage I: 30 (73%) (19 Ia, seven Ic, four I unknown); stage II: seven (17%) (two IIa, five IIC); stage III: three (7%) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 29 publications
1
35
1
3
Order By: Relevance
“…Although the extent of the initial surgical procedure is still controversial and not standard, some authors reported higher relapse rates in cases of conservative surgery and better survival in cases with radical surgery. 11 In patients of childbearing age with desire for future fertility, fertility saving surgery seems to be acceptable. However, a comprehensive staging procedure should again be performed since the pattern of spread seems to include peritoneal surfaces similar to epithelial ovarian carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Although the extent of the initial surgical procedure is still controversial and not standard, some authors reported higher relapse rates in cases of conservative surgery and better survival in cases with radical surgery. 11 In patients of childbearing age with desire for future fertility, fertility saving surgery seems to be acceptable. However, a comprehensive staging procedure should again be performed since the pattern of spread seems to include peritoneal surfaces similar to epithelial ovarian carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen overproduction is also responsible for endometrial hyperplasia and concomitant endometrial cancer, which according to the literature occur in 32%-85% and 3%-22% of cases, respectively (33,34). Uterine cancer is nearly always a low-grade, low-stage endometrioid adenocarcinoma (35).…”
Section: Pure Sex Cord Tumors Adult and Juvenile Granulosa Cell Tumorsmentioning
confidence: 99%
“…Nous n'avons pas retrouvé ce facteur pronostique dans notre série. Le stade est un des rares facteurs qui fait l'objet d'un consensus [26,[28][29][30] (Tableau 1) : la médiane de survie pour les stades III et IV est de cinq ans, alors qu'elle est supérieure à 25 ans pour les stades I. Un stade avancé serait plus souvent impliqué dans la survenue de récidive et serait prédictif d'une tumeur hautement proliférative [27]. Ainsi, quatre des six patientes, avec une récidive que nous rapportons, présentaient une extension tumorale extraovarienne d'emblée [11].…”
Section: Facteurs Pronostiquesunclassified